Intranasal Transplantation of Human Neural Stem Cells Ameliorates Alzheimer's Disease-Like Pathology in a Mouse Model - Lu, Mei-Hong; Ji, Wen-Li; Chen, Hong; Sun, Yan-Yun; Zhao, Xiu-Yun; Wang, Fen; Shi, Yi; Hu, Yan-Ning; Liu, Bo-Xiang; Wu, Jing-wen; Xu, De-En; Zheng, Jia-Wei; et al. (Frontiers in Aging Neuroscience, 2021)
Alzheimer's disease (AD) is a neurodegenerative disorder characterized by memory impairments, which has no effective therapy. Stem cell transplantation shows great potential in the therapy of various disease. However, the application of stem cell therapy in neurological disorders, especially the ones with a long-term disease course such as AD, is limited by the delivery approach due to the presence of the brain blood barrier. So far, the most commonly used delivery approach in the therapy of neurological disorders with stem cells in preclinical and clinical studies are intracranial injection and intrathecal injection, both of which are invasive. In the present study, we use repetitive intranasal delivery of human neural stem cells (hNSCs) to the brains of APP/PS1 transgenic mice to investigate the effect of hNSCs on the pathology of AD. The results indicate that the intranasally transplanted hNSCs survive and exhibit extensive migration and higher neuronal differentiation, with a relatively limited glial differentiation. A proportion of intranasally transplanted hNSCs differentiate to cholinergic neurons, which rescue cholinergic dysfunction in APP/PS1 mice. In addition, intranasal transplantation of hNSCs attenuates β-amyloid accumulation by upregulating the expression of β-amyloid degrading enzymes, insulin-degrading enzymes, and neprilysin. Moreover, intranasal transplantation of hNSCs ameliorates other AD-like pathology including neuroinflammation, cholinergic dysfunction, and pericytic and synaptic loss, while enhancing adult hippocampal neurogenesis, eventually rescuing the cognitive deficits of APP/PS1 transgenic mice. Thus, our findings highlight that intranasal transplantation of hNSCs benefits cognition through multiple mechanisms, and exhibit the great potential of intranasal administration of stem cells as a non-invasive therapeutic strategy for AD.